2019
DOI: 10.3390/ijerph16203948
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Correlates of Health-Related Quality of Life among Women Living in Informal Settlements in Kenya

Abstract: Informal settlements (slums)—defined as residential areas lacking durable housing; sufficient living and public spaces; access to basic infrastructure, water, sanitation, and other services; and secure tenancy—are presumed to be poor health environments. Research in Kenya suggests that residents of these settlements have the worst health outcomes of any population, yet there is a paucity of research focused on the health and well-being of these residents. Even less attention is given to the role played by envi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…Environmental factors. Research has shown that lack of access to water and sanitation may be associated with poor health outcomes for women in informal settlements [17,23,25,57,58]. Access to water and sanitation are also used as alternative or additional sociodemographic or wealth measures in these settlements [59,60].…”
Section: Methodsmentioning
confidence: 99%
“…Environmental factors. Research has shown that lack of access to water and sanitation may be associated with poor health outcomes for women in informal settlements [17,23,25,57,58]. Access to water and sanitation are also used as alternative or additional sociodemographic or wealth measures in these settlements [59,60].…”
Section: Methodsmentioning
confidence: 99%
“…In Kenya, studies on HRQOL have been conducted among various populations such as children in Schistosoma haematobium-endemic areas [ 30 ], people living with irrigation schemes [ 31 ], women living in informal settlements [ 32 ], patients undergoing antiretroviral treatment [ 33 , 34 , 35 ], patients on maintenance hemodialysis [ 36 ] and patients who have undergone cataract surgery [ 37 ]. However, a study on HRQOL among healthcare workers in Kenya is yet to be conducted.…”
Section: Introductionmentioning
confidence: 99%
“…Factors included dirty public or school toilets, 62,130,154,172,177,233 open defecation fields, 56,175,176,181 feces within community spaces, 176 foul odors from toilets, 174 urinating on another person's urine, 170 using shared toilet seats at school, 209,227 consuming fish from canals where people defecated, 140 unhygienic defecation practices and insufficient solid waste management, 104,108,163,212,225,226 and food contamination because of latrine proximity to cooking areas. 130 Mental Health Mental health is increasingly engaged in research on water 62,76,82,86,94,109,149,151,156,163,178,184,187,188,191,195,257,260,261,266,275 and sanitation. Water-related stress, anxiety, depression, or fear were reported by women in Ethiopia regarding water-related illnesses; 94 in Bolivia, 218 Brazil, ...…”
Section: Illness and Infirmitymentioning
confidence: 99%
“…2 Toilet access in Kenya was associated with better mental health and well-being among women. 275 Women who received latrines in Mozambique reported that they decreased their stress, 161 and women in India reported that private latrines helped them to overcome the embarrassment, shame, and anxiety of open defecation. 125…”
Section: Illness and Infirmitymentioning
confidence: 99%